2008
DOI: 10.1111/j.1365-2125.2008.03172.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on hs‐CRP in acute coronary syndrome

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Markers of inflammation are being investigated as predictors of coronary ischaemic events. All major statins have shown almost similar and significant efficacy in reducing C-reactive protein (CRP) concentrations in acute coronary syndrome (ACS), but atorvastatin was used in a high dose (80 mg).• This study was designed to evaluate the effect of a lower dose (20 mg) of atorvastatin on hs-CRP concentrations in patients with ACS. WHAT THIS STUDY ADDS• A lower dose of ator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
(17 reference statements)
1
8
0
1
Order By: Relevance
“…29 In this study, high-dose atorvastatin significantly increased HDL and decreased LDL levels, which was consistent with other similar studies. [30][31][32] In this study, consumption of high-dose statins could significantly reduce the amount of hs-CRP compared to lower doses. Meanwhile, in the studies conducted by Macin and Vasilieva it was revealed that CRP level in ACS decreased quickly after taking atorvastatin.…”
Section: Discussionmentioning
confidence: 96%
“…29 In this study, high-dose atorvastatin significantly increased HDL and decreased LDL levels, which was consistent with other similar studies. [30][31][32] In this study, consumption of high-dose statins could significantly reduce the amount of hs-CRP compared to lower doses. Meanwhile, in the studies conducted by Macin and Vasilieva it was revealed that CRP level in ACS decreased quickly after taking atorvastatin.…”
Section: Discussionmentioning
confidence: 96%
“…High hsCRP value more in younger age group explains occurrence of high premature Coronary Artery Disease in our study and so in India 19 . So screening of population in the younger age group for high hs-CRP may be very useful as targeting those with statin therapy can reduce the mortality, morbidity and overall burden of health care 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had evaluated interrelationships between CRP and metabolic syndrome, which is comprised of waist circumference, dyslipidaemia, abnormal glucose tolerance and BP 22 it showed that metabolic syndrome is associated with increased levels of CRP (36). CRP is considered as important biomarker in metabolic syndrome has been proved 23 Lowering hs-CRP by lipid lowering agents like statins had shown a beneficial effect on cardiovascular risk in many previous studies (37-39) Ankur et al 24 found a greater reduction in hs-CRP up to 22-40% in patients with acute coronary syndrome treated with atorvastatin for 4 weeks. This beneficial effect was independent of statin effects on cholesterol.…”
Section: Discussionmentioning
confidence: 99%